Noisy Robots? Comparison of Occupational Noise Levels Between Robotic-Assisted and Conventional Total Knee Arthroplasty - Laurent Willemot, MD, PhD; Alisdair Gilmour, FRCS; Jonathan Mulford, FRACS; David Penn, FRACS (Arthroplasty Today)
Background: Noise exposure during surgery is a known occupational hazard, impacting staff hearing and surgical outcomes. Despite guidelines such as the Australian Work Health and Safety Act, noise safety remains largely neglected in orthopaedic surgery. Anecdotally, the introduction of robotic-assisted arthroplasty has contributed to increased noise production. This research article aims to investigate the role of robots in noise levels during arthroplasty. Methods: In this prospective observational study, we collected noise exposure data during total knee arthroplasty with and without robotic assistance. Noise levels were measured using a smartphone placed in the surgeon’s breast pocket. Patient demographics and surgical details were collected for subgroup analysis. Mean (LAeq), time-weighted average, and peak noise levels, as well as dose equivalent were calculated to quantify the exposure. Results: A total of 65 knee arthroplasty sound recordings were included with a mean noise level of 82.0 dB (standard deviation [SD]: 3.9). Robotic-assisted surgeries exhibited significantly higher levels than using the conventional technique: 82.4 (SD: 3.2) vs 78.4 dB (SD: 3.8) (<0.0001). These values exceed some of the recommended guidelines. Peak exposure levels were similar in both categories at 109.6 (SD: 2.7) and 110.7 dB (SD: 4.3), remaining below the safety threshold. Conclusions: This study highlights the potential for harmful noise exposure in orthopaedic surgery, emphasizing the contribution of robotic-assisted procedures. Our findings indicate noise levels approximate or exceed international safety guidelines. The results support the wearing of personal protective hearing equipment, and other preventative strategies. Our study provides insights into an underappreciated aspect of orthopaedic surgery.